A Holistic View to Develop Descriptive Sheets for Argentinean Clover and Eucalyptus Unifloral Honey - Ciappini, María C.; Calviño, Amalia (Current Nutrition & Food Science, 2020)
Background: Honey is a complex natural product that varies not only in sensory properties but also in chemical composition. The apiculture industry is interested in offering unifloral honey with specific palynological, physicochemical and sensory characteristics. However, to the best of our knowledge, no proper study has been reported in Argentina in this regard so far. Objective: The aim of this study was to develop descriptive sheets analyzing and compiling previous palynological, physicochemical and sensory data obtained from Argentine eucalyptus and clover unifloral honeys. Methods: The analysis included predominant and main secondary pollens; physicochemical characteristics as moisture content, acidity, ash content, electrical conductivity, fructose, glucose, maltose and sucrose, optical rotation and colour; antioxidant indicators as DPPH, TEAC, FRAC, OH; content of phenolic and flavonoids compounds and the main sensory descriptors like colour, smell, aromatic notes, sweetness and persistence. Results: The analysis was made by gathering 30 Eucalyptus honey (Eucalyptus spp.) and 55 clover honey (Trifolium sp.). Forty-one morphological pollen types were recognized. The set of physicochemical measures for honey met quality specifications for international marketing. Colour and odour intensity, higher for eucalyptus honey, were identified as the main differentiating sensory attributes. Conclusion: An holistic analysis of all these properties allows to determine quality and certification of Argentinean eucalyptus and clover unifloral honey. The intervals of variation of selected palynological, physicochemical and sensory variables gathered in the descriptive sheets allow us to decide whether or not a sample of honey can be classified as belonging to one of these floral origins.
Keywords: descriptive sheets